2020
DOI: 10.1021/jacs.0c02355
|View full text |Cite
|
Sign up to set email alerts
|

On the Nature of C(sp3)–C(sp2) Bond Formation in Nickel-Catalyzed Tertiary Radical Cross-Couplings: A Case Study of Ni/Photoredox Catalytic Cross-Coupling of Alkyl Radicals and Aryl Halides

Abstract: The merger of photoredox and nickel catalysis has enabled the construction of quaternary centers. However, the mechanism, role of the ligand, and effect of the spin state for this transformation and related Ni-catalyzed cross-couplings involving tertiary alkyl radicals in combination with bipyridine and diketonate ligands remain unknown. Several mechanisms have been proposed, all invoking a key Ni­(III) species prior to undergoing irreversible inner-sphere reductive elimination. In this work, we have used open… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
156
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 185 publications
(173 citation statements)
references
References 46 publications
17
156
0
Order By: Relevance
“…Both cyclic and acyclic a-silyl amines worked well to deliver the corresponding a-aryl substituted gamino acid esters in moderate to excellent yields.Especially, the substrates containing pharmaceutically relevant moieties such as piperidine,p yrrolidine,m orpholine and piperazine, which are among the most frequent N-heterocyclic functions employed in drugs,w ere incorporated smoothly with decent yields (4,(7)(8)(9)(10). Thereaction was not only limited to aliphatic a-silyl amines,b ut also be suitable for aromatic amines (13)(14). a-Silyl secondary amine with af ree NH group was not compatible (15), which made the reaction quite messy and only al ittle of radical precursor recovered (18 %f rom crude 1 HNMR spectrum).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both cyclic and acyclic a-silyl amines worked well to deliver the corresponding a-aryl substituted gamino acid esters in moderate to excellent yields.Especially, the substrates containing pharmaceutically relevant moieties such as piperidine,p yrrolidine,m orpholine and piperazine, which are among the most frequent N-heterocyclic functions employed in drugs,w ere incorporated smoothly with decent yields (4,(7)(8)(9)(10). Thereaction was not only limited to aliphatic a-silyl amines,b ut also be suitable for aromatic amines (13)(14). a-Silyl secondary amine with af ree NH group was not compatible (15), which made the reaction quite messy and only al ittle of radical precursor recovered (18 %f rom crude 1 HNMR spectrum).…”
Section: Resultsmentioning
confidence: 99%
“…Alternatively,t he Ni III Int D could also be formed by the recombination of radical B to Ni II Int F arising from the oxidative addition of Ar-X with Ni 0 (path b). [13] This process has two major challenges:1)compared with secondary or tertiary alkyl radicals,primary alkyl radicals are much less congested and thus,more reactive to participate the competitive two-component cross-coupling to delivery undesired byproduct 5; [14] 2) the thermodynamically favorable SET between alkyl radical [15] and the reduced state of PCC À (the oxidative potential for commonly used PCC À ranges from À0.8 to À2.2 V vs.SCE in CH 3 CN) [7a] facilitates undesired Giese-type hydroalkylation byproduct 6. [16] Besides,p rotodehalogenation of aryl halide under metallaphotoredox conditions is another obstacle, [9d] which could not be neglected.…”
Section: Introductionmentioning
confidence: 99%
“…This nickel catalytic cycle [Ni(0), Ni(I), Ni(III)] is different to that shown in Scheme 61 [Ni(0), Ni(I), Ni(II), Ni(III)], but both are plausible and it is difficult to determine which is in operation. Towards this, Molander and Gutierrez recently reported an interesting computational investigation that assessed the feasibility of different possible mechanisms for tertiary radicals in nickel/photoredox dual catalysis and concluded that multiple mechanisms are plausible, and which one is in operation is both substrate and ligand dependant [ 153 ].…”
Section: Reviewmentioning
confidence: 99%
“…This extremely powerful combination opens up unprecedented chemical transformations that are well‐suited to applications in complex settings on account of the mild reaction conditions [131, 137, 138] . Key to the success of this approach is the activation of transition‐metal complexes by a photocatalyst, either through redox modulation or energy transfer pathways, triggering mechanistic steps that would not be operative under transition‐metal catalysis alone [139–144] …”
Section: Photoinduced Electron Transfer In Peptide Macrocyclisationmentioning
confidence: 99%
“…[131,137,138] Key to the success of this approachi st he activation of transition-metal complexes by a photocatalyst, either through redox modulation or energy transfer pathways, triggering mechanistic steps that would not be operative under transition-metal catalysis alone. [139][140][141][142][143][144] The Sciammetta group disclosed am ethodology for the etherification of peptidic alcohols with aryl bromides by C(sp 2 )ÀOc ross-coupling under dual photoredoxa nd nickel catalysis. [145] In addition to intermolecular ether formation, the reaction conditions were also shown to be amenable to macrocyclisation of as eries of N-terminal bromobenzamides, via aryl etherification of C-terminal serine derivatives.…”
Section: Peptidemacrocyclisation Under Photoredox Catalysismentioning
confidence: 99%